Postpartum oral glucose tolerance test in mothers of macrosomic infants as a retrospective diagnostic method of gestational diabetes - Cárdenas, Joel (2004)
OBJECTIVE: To assess the relationship between the postpartum oral glucose tolerance test (PPOGTT) and fetal macrosomia and its usefulness as a retrospective diagnostic method of gestational diabetes. DESIGN: Prospective case –control study. MATERIAL AND METHODS: Mothers with macrosomic infants (n = 71) and controls (n = 71) were studied. PPOGTT was determined in all of them using 100 grams of glucose 8 to 48 hours postpartum. Data processing used SPSS 10,0. RESULTS: Abnormal PPOGTT is a risk factor to fetal macrosomia with an adjusted odds ratio (OR) 5,9 (95%CI 2,6-13,4). There is association with a previous history of macrosomia OR 15,7 (95CI 1,9-123,6) and with prenatal control OR 5,7 (95%CI 1,2-26,8). CONCLUSIONS: PPOGTT may identify a subset of women with macrosomic infants who had gestational diabetes; we may consider it a retrospective diagnostic test.